Development of 1,3,4-Oxadiazole Derived Antifungal Agents and Their Application in Maize Diseases Control - Yao, Lin; Zhang, Guanghua; Yu, Lili; Liu, Shaojing; Wang, Xiaoku; Fan, Tao; Kang, Hui; Feng, Wenzhi (Frontiers in Plant Science, 2022)
Maize is an important food crop and its fungal disease has become a limiting factor to improve the yield and quality of maize. In the control of plant pathogens, commercial fungicides have no obvious effect on corn diseases due to the emergence of drug resistance. Therefore, it is of great significance to develop new fungicides with novel structure, high efficiency and low toxicity to control maize diseases. In this paper, a series of 1,3,4-oxadiazole derivatives were designed and synthesized from benzoyl hydrazine and aromatic aldehydes through condensation and oxidation cyclization reaction. The antifungal activities of oxadiazole derivatives against three maize disease pathogens were evaluated by mycelium growth rate method in vitro. The results indicated that most of the synthesized derivatives exhibited positive antifungal activities. Especially against E. turcicum, several compounds demonstrated significant antifungal activities and their EC50 values were lower than carbendazim. The EC50 values of compounds 4k, 5e, 5i and 5k were 50.48, 47.56, 47.05, 32.25 μg/mL, respectively, and the positive drug was 102.83 μg/mL. The oxadiazole derivatives had almost no cytotoxicity to MCF-7. Preliminary mechanism research showed that compounds 4k, 5e and 5k could induce the hyphae of E. turcicum to shrink and collapse obviously. Molecular docking simulation manifested that compounds 5e and 5k could form hydrogen bonds with amino acid residues TRP-173 and TYR-58 through oxadiazole ring, which explained the possible mechanism of binding between inhibitor and SDH target protein. This study showed that 1, 3, 4-oxadiazole derivatives were worthy for further attention as potential antifungal agents for the control of maize diseases.